Genome-Wide Mapping of Structural Variations Reveals a Copy Number Variant That Determines Reproductive Morphology in Cucumber. Issue 6 (22nd May 2015) - Zhang, Zhonghua; Mao, Linyong; Chen, Huiming; Bu, Fengjiao; Li, Guangcun; Sun, Jinjing; Li, Shuai; Sun, Honghe; Jiao, Chen; Blakely, Rachel; Pan, Junsong; Cai, Run; et al.
Abstract : Genome-wide scanning of large size sequence changes revealed a tandem duplication of a DNA segment that gives rise to cucumbers bearing only female flowers. Abstract: Structural variations (SVs ) represent a major source of genetic diversity. However, the functional impact and formation mechanisms of SVs in plant genomes remain largely unexplored. Here, we report a nucleotide-resolution SV map of cucumber ( Cucumis sativas ) that comprises 26, 788 SVs based on deep resequencing of 115 diverse accessions. The largest proportion of cucumber SVs was formed through nonhomologous end-joining rearrangements, and the occurrence of SVs is closely associated with regions of high nucleotide diversity. These SVs affect the coding regions of 1676 genes, some of which are associated with cucumber domestication. Based on the map, we discovered a copy number variation (CNV ) involving four genes that defines the Female ( F ) locus and gives rise to gynoecious cucumber plants, which bear only female flowers and set fruit at almost every node. The CNV arose from a recent 30.2-kb duplication at a meiotically unstable region, likely via microhomology-mediated break-induced replication. The SV set provides a snapshot of structural variations in plants and will serve as an important resource for exploring genes underlying key traits and for facilitating practical breeding in cucumber.